Ajem Pekang : Analisis Pesan Dakwah pada Tradisi Masyarakat Pandalungan di Desa Ranuyoso - Achmad Farid; Bambang Subahri (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2021)
Ajem pekang is a side dish of chicken on a cone with its distinctive shape, which is skewered with a stick of bamboo resembling satay. Ajem Pekang is full of the meaning of religiosity and spirituality of the Pandalungan community. Ajem Pekang is a symbolic central form in the traditional rituals of the Pandalungan community. This research is a qualitative research that was compiled based on data collection with interviews, observations and some documentation collected during the religious rituals of the Pandalungan community. The conclusion of this study is the existence of the Pandalungan custom by reason of the religious values ​​contained in it. These values ​​are in line with the values ​​of humanity and Pancasila as Indonesian citizens who believe in the one and only God. Furthermore, ajem pekang is not necessarily limited to a side dish served in the middle of a mound of rice on a mere tray, but inside it has semiotic value and meaning in the form of symbolization.